EKSPRESI AKSARA INCUNG KERINCI DALAM PENCIPTAAN SENI KRIYA - Husni Mubarat (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Incung Kerinci script is one of the Kerinci community culture in ancient times. Incung Kerinci script is an ancient manuscript that used by the tribe Kerinci on previously as a vehicle to write literature, customary law, and incantations written on bark, buffalo horns, bamboo and palm leaves. Incung Kerinci script formed by straight lines, broken and curved stuck. The slope of the line forming the letter was an average of 45 °. As a cultural product of the past, Incung Kerinci script always continue to be developed, in order to remain sustainable existence in modern life are increasingly sinking value of the local culture. The creation of this work passed three stages, namely exploration, design, and realization through the search of new forms of art craft, creative, and innovative, by not leaving the principles of modern art. Manifestations of the work using media of wood, sawdust, brass, iron, and bamboo. The technique used is: carving techniques, techniques nock, chisel technique, technique paste, polishing techniques, engineering lathe, welding techniques and grafting techniques. In the embodiment of this work more emphasis on the value of expression without leaving the meaning, message, and symbols. Meaning, messages and symbols contained in the artworks created this craft, is the transformation of cultural values and traditions of the people of Kerinci. The creation of works of art crafts can be a medium as Incung Kerinci script development, to the next generation. The creation of this craft artwork can also give insight to the creators of art, that in the context of the modern era, the essence of culture and local potential can be used as a source of creation is a work of art craft of personal expression.